The Utilization of Digital Media in Indonesian Language Learning at Elementary Schools: A Systematic Literature Review - Putri Hana Pebriana; Maliny Putri; Herlina Safitri; Miftahul Jannah; Suci Rahmadani; Sintia Aprilia; Zami Akbar; Siti Rahma Mailani (The Future of Education Journal, 2026)
Indonesian language learning at the elementary school level plays a crucial role in developing students' language skills from an early age. However, in practice, the learning process is still often conducted conventionally, which fails to effectively enhance student motivation and active engagement. The advancement of digital technology offers an opportunity to address these issues through the use of more varied and interactive digital learning media. This study aims to examine the utilization of digital learning media in Indonesian language learning at elementary schools through a Systematic Literature Review (SLR) approach. The research method involved searching for and analyzing relevant scholarly articles through Google Scholar and accredited national journals. The articles analyzed were selected based on predefined inclusion and exclusion criteria. The findings show that digital learning media, such as learning videos, interactive multimedia, educational applications, and digital teaching materials, are widely used in Indonesian language learning at elementary schools. The use of these media has been proven to enhance student motivation, engagement, learning outcomes, and language skills. Thus, digital learning media can serve as an effective alternative in improving the quality of Indonesian language learning at elementary schools.